Factors associated with diarrhea and acute respiratory infection in children under two years of age in rural Bangladesh - Md Barkat Ullah; Malay K. Mridha; Charles D. Arnold; Susana L. Matias; Md Showkat A. Khan; Zakia Siddiqui; Mokbul Hossain; Rina Rani Paul; Kathryn G. Dewey (BMC, 2019)
Abstract Background Diarrhea and acute respiratory infection (ARI) are major causes of child mortality. We aimed to identify risk factors associated with diarrhea and ARI among children under 2 years of age in rural northern Bangladesh. Method We collected information on diarrhea and ARI in the previous 14 days and the previous 6 months at 6, 12, 18 and 24 months of age as part of a longitudinal, cluster randomized effectiveness trial, the Rang-Din Nutrition Study which enrolled 4011 pregnant women at ≤20 gestational weeks. Women and their children were followed up until 2 years postpartum. Information on household socioeconomic status, type of toilet, garbage disposal system, food insecurity, number of under-five children in the household, type of family, maternal characteristics and child characteristics was collected at baseline and/or at 6, 12, 18 and 24 months postpartum. Data on newborn health and feeding behaviors were collected within 72 h of delivery. Associations between potential risk factors and morbidity prevalence outcomes were assessed using logistic regression controlling for potential confounders. Results Out of 3664 live born children, we collected information from ~ 3350 children at 6, 12, 18 and 24 months of age. Diarrhea in the previous 14 days, and in the previous 6 months, was associated with maternal depression score and food insecurity; diarrhea in the previous 6 months was also associated with family type (nuclear vs. joint). ARI in the previous 14 days was associated with maternal depression score, type of toilet and garbage disposal, household food insecurity and sex. Cough or nasal discharge in the past 6 months was associated with maternal depression score, type of toilet and garbage disposal, household food insecurity, sex and perceived overall physical condition of the infant after birth. Conclusion Maternal depression and food insecurity appear to be important risk factors for diarrhea and respiratory infection among children under 2 years of age in this setting. These findings suggest that policies and programs that include strategies to address maternal mental health and household food insecurity may contribute to improved child health. Trial registration The trial was registered with the US National Institutes of Health at ClinicalTrials.gov, # NCT01715038, with registration completed October 26, 2012.